An inhibitor of chondroitin sulfate proteoglycan synthesis promotes central nervous system remyelination - Michael B. Keough (Nature Portfolio, 2016)
Chondroitin sulfate proteoglycans (CSPGs) secreted by astrocytes are known to inhibit OPC differentiation and remyelination. Here, the authors identify a novel CSPG synthesis inhibitor and find it can rescue OPC differentiation in vitroand accelerate remyelination in mice following focal demyelination.